2015
DOI: 10.1152/ajpendo.00094.2014
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase-1B contributes to LPS-induced leptin resistance in male rats

Abstract: Borges BC, Rorato RC, Uchoa ET, Marangon PB, Elias CF, Antunes-Rodrigues J, Elias LL. Protein tyrosine phosphatase-1B contributes to LPS-induced leptin resistance in male rats. Am J Physiol Endocrinol Metab 308: E40 -E50, 2015. First published October 28, 2014 doi:10.1152/ajpendo.00094.2014.-Leptin resistance is induced by the feedback inhibitors tyrosine phosphatase-1B (PTP1B) and decreased Src homology 2 domain-containing tyrosine phosphatase-2 (SHP-2) signaling. To investigate the participation of PTP1B an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…Furthermore, PTP1B inhibition seems to pose a risk for hyperinflammation in case of a simultaneous infection, indicated by the increased PTP1B inhibition resulting in an extremely increased IL-8 release triggered by the combination of LPS and the PTP1B inhibitor. Accordingly, PTP1B has previously been described as an important negative regulator of LPS-induced inflammation in various cell types 4951 , functioning as safety mechanism preventing hyperinflammation. If regular exposure to PTP1B inhibiting welding fumes could end in clinically relevant hyperinflammation as reaction to pulmonary or systemic infections is unclear and needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PTP1B inhibition seems to pose a risk for hyperinflammation in case of a simultaneous infection, indicated by the increased PTP1B inhibition resulting in an extremely increased IL-8 release triggered by the combination of LPS and the PTP1B inhibitor. Accordingly, PTP1B has previously been described as an important negative regulator of LPS-induced inflammation in various cell types 4951 , functioning as safety mechanism preventing hyperinflammation. If regular exposure to PTP1B inhibiting welding fumes could end in clinically relevant hyperinflammation as reaction to pulmonary or systemic infections is unclear and needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibits adipocyte synthesis, and thereby reduces body weight. Therefore, leptin plays a key role in regulating the physiological processes of food intake, glucose homeostasis, and energy intake and consumption [7,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic low-grade inflammation is associated with leptin and insulin resistance, which contributes to the establishment of obesity and its comorbidities, such as type 2 diabetes, cancer, and cardiovascular diseases [ 1 ]. We have previously demonstrated that low-grade inflammation induced by repeated injections of the Gram-negative bacterial lipopolysaccharide (6 daily doses of LPS) induces tolerance to the hypophagic effect of the endotoxin [ 2 , 3 ]. The endotoxin failure to reduce food consumption and body weight in LPS-tolerant rats is associated with unresponsiveness to leptin to phosphorylate the signal transduction and activator of transcription 3 (pSTAT3) protein in the hypothalamic nuclei crucial for the control of the energy homeostasis, such as the paraventricular (PVN) and arcuate (ARC) nuclei [ 2 ].…”
Section: Introductionmentioning
confidence: 99%